Gerakan Pencegahan Penyakit Ginjal Kronis Kearah Peningkatan Pengetahuan dan Kesehatan Masyarakat : Gerakan Pencegahan Penyakit Ginjal Kronis - Tasnim, Tasnim; Saafi, La Ode; Munir, Sanihu; Fitri, Fitri; Karuniawati , Kadek Ayu (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2024)
Hypertension and diabetes millitus are risk factors for chronic kidney disease and are still a problem in the Abeli Sub-District, including in Abeli Village. Chronic Kidney Disease can be prevented, one of which is physical activity. Increasing knowledge about chronic kidney disease is also very important to shape behavior towards preventing chronic kidney disease. This community development aims to increase community knowledge and health in Abeli village in order to prevent chronic kidney disease. The solutions offered include healthy exercise movements and health education about chronic kidney disease, as well as distribution of leaflets about chronic kidney disease. The movement to prevent chronic kidney disease was carried out in May 2024, and was attended by 27 PKK women in Abeli Village. PKM participants from PKK mothers were aged between 33-69 years. Most of the participants had junior high school education (35.3%), and the remainder had high school education (23.5%), bachelor's degree (17.6%), 11.8% elementary school education, and 11.8% had no school education. The results of this service activity showed that there was a significant increase in participants' knowledge about chronic kidney disease (p value <0.0001). The average knowledge before the health education was 3.94 ± SD 2.08 and after the health education the average increased to 9.18 ± SD 1.02. Community service activities with exercise movements and health education as well as distribution of leaflets about chronic kidney disease can increase participants' knowledge about chronic kidney disease. Increased knowledge will shape behavior towards preventing chronic kidney disease.